Dispersion of hydrogen release in a naturally ventilated covered car park. (3rd September 2020) - Hussein, H.; Brennan, S.; Molkov, V.
Abstract: By necessity hydrogen-powered vehicles will be parked in covered and underground car parks. This has implications for the safety of life and property, and the development of regulations, codes and standards governing passenger vehicles and car parks. This study utilises Computational Fluid Dynamics (CFD) to investigate unignited hydrogen release and dispersion from 700 bar onboard storage in a naturally ventilated covered car park. The impact of leak diameter and angle of leak direction on the formation of the flammable cloud and the implications for vehicle passengers, first responders and car park ventilation are discussed. A typical car park with dimensions LxWxH = 30 × 28.6 × 2.6 m with two opposing vents based on the British Standard (BS 7346–7:2013) was considered. Releases through three different Thermally Activated Pressure Relief Devices (TPRD) with diameters of 3.34, 2.00 and 0.50 mm were compared, to understand the gas dispersion, specifically the dynamics of envelope formation for 1%, 2% and 4% vol of hydrogen. Concentrations in the vicinity of the vehicle and of the vents were of particular interest. It was shown how blowdown through a TPRD diameter of 3.34 mm leads to the formation of a flammable cloud throughout the majority of the car park space in less than 20 s. However, such a flammable envelope was not observed to the same extent for a TPRD diameter of 2 mm and the flammable envelope is negligible for a 0.5 mm diameter TPRD. A release through a 2 mm TPRD diameter resulted in concentrations of 1% hydrogen along the length of the car park ceiling within 20 s, which should activate hydrogen sensors, in contrast an upward release through a 0.5 mm diameter led to concentrations of 1% reaching a very limited area of the ceiling. Downward TPRD release angles of 0°, 30° and 45° were considered, and while an angle of 30° and 45° directed the hydrogen away from the car body, a downward release at 0° briefly surrounded the car doors and passenger escape routes with a flammable cloud. The study highlights the importance of release angle and demonstrates that a TPRD diameter of 0.5 mm is safer for the particular scenario considered. Larger diameter TPRDs have previously been shown to be unacceptable from a pressure peaking perspective and this study questions their use safety in a naturally ventilated covered car park. Highlights: Numerical investigation of release from onboard storage in a covered car park. Release and dispersions from a range of TPRD diameters is simulated. A 0.5 mm diameter TPRD was found to be inherently safer for 700 bar storage. The angle of TPRD release was shown to have implications for passenger egress. Results support the inherently safe design of hydrogen fuel cell vehicles.